Writing for emerging sociologists - Harris, Angelique; Tyner-Mullings, Alia (SAGE Pub., 2013)
A writing guide designed for upper-level sociology undergraduate students and graduate students, this instructional text introduces students to the variety of writing projects that sociologists undertake, while also providing instruction on grammar and composition. It will provide students with practical knowledge concerning topics such as: peer reviewed journal manuscripts, book reviews, grant proposals, and field notes. What makes this book unique is that it offers useful advice and instruction for sociology college students whether they plan on entering the academy or the private, non-profit, or government sectors. Writing for Emerging Sociologists uses writing as a tool to help students learn not only about sociology as a field of study, but also the practice of sociology.